Indian studies : essays presented in memory of Prof. Niharranjan Ray - Sanyal, Hitesranjan, 1940-; Ray, S. C. (Sunil Chandra), 1924-; Ray, Niharranjan, 1903-1981. (Delhi : Caxton, 1984)
Commemorative volume for Niharranjan Ray, 1903-1981, Indic historian; comprises articles on his life and works and Indic civilization.
Includes bibliographical references.
Keywords: Ray, Niharranjan, -- 1903-1981.; India -- Civilization; India -- Antiquities